Development of 5 Weather Theme Videoscribe Learning Media to Improve Learning Motivation of Class III Students at SDN 132406 Tanjung Balai - Sari, Widya; Landong, Ahmad (Widyagogik, 2023)
This development research aims to (1) development  videoscribe learning media in learning theme 5 Weather, (2) find out the feasibility of developing videoscribe media in increasing student learning motivation. This research is a type of research and development Research and Development (RD) using the ADDIE development model which consists of 5 stages, namely. Analysis (Analysis). Design (Design). Development (Development), Implementation (Implementation) and Evaluation (Evaluation).The instruments used in this study were educational practitioner questionnaires, media expert questionnaires, material expert questionnaires, student response questionnaires and teacher response questionnaires to determine the feasibility of the developed 5 weather theme videoscribe media.Based on the validation results from educational practitioners, a percentage of 98.8% was obtained with the "Very Eligible" criteria. From the validation results of media experts, it was obtained an average percentage of 96.6% with the criteria of "Very Eligible". From the results of the material expert validation, an average percentage of 94.5% was obtained with the criteria of "Very Eligible". From the validation results of student responses, a percentage of 95.7% was obtained with the criteria "Very Eligible" and from the validation results of the teacher's response, a percentage of 98% was obtained with the criteria "Very Eligible". From the assessment obtained, it can be said that the 5 weather theme videoscribe media developed "Very Eligible" is used in the learning process.